Suppression of photosynthetic capacity, biomass and relative chlorophyll content of selected host species affected by parasitic plant Cassytha filiformis L. - Aisyah Zahidah, Abd Rani; Siti Rubiah, Zainuddin; Isa, Ipor; Kevin Muyang Tawie, Sulok (Malaysian Society of Plant Physiology, 2017)
Cassytha filiformis infected its host through haustorium to absorb nutrients. Due to its parasitic property and growth habit with extensive coverage, C. filiformis has a great potential as cover crops in oil palm plantation. The extensive establishment is able to control weed encroachment and suppress its aggressiveness on crops. A study was conducted to determine the suppression of photosynthetic capacity, biomass and relative chlorophyll content of seven crop species infected by C. filiformis. The seven species included Asystasia intrusa Bl., Colocasia esculenta (L.) Schott, Ipomoea aquatica Forsk., Ischaemum muticum L., Manihot esculenta Crantz, Merremia umbellata (L.) Hall, and Mikania micrantha H.B.K. The photosynthetic rate of M. micrantha was suppressed by 95.62 % while A. intrusa, I. aquatica, M. esculenta, C. esculenta and M. umbellata were suppressed at 94.29 %, 84.00 %, 80.81 %, 67.55 % and 67.07 %, respectively. The lowest suppression of the photosynthetic rate was for I. muticum which was 43.06 %. The rate of suppression of all species by C. filiformis could probably be related to the morphological and physiological characteristics of the species. A strong relationship between photosynthesis and stomatal conductance of 0.92 for infected and 0.97 for uninfected species were recorded. Similarly, the biomass and chlorophyll content reduction were positively correlated with photosynthetic rate depending on the level of infection by C. filiformis with values of 0.82 and 0.95, respectively. Therefore, C. filiformis has the potential to be an effective biological control agent.